1993
DOI: 10.1785/bssa0830051442
|View full text |Cite
|
Sign up to set email alerts
|

Fault plane solutions and relocations of recent earthquakes in Middleton Place Summerville Seismic Zone near Charleston, South Carolina

Abstract: The Middleton Place Summerville Seismic Zone (MPSSZ), located about 20 km northwest of Charleston is the most active seismic zone in South Carolina. Between 1980 and 1991, 58 events with Md 0.8 to 3.3 were recorded in MPSSZ. They lie in a diffuse area of 11 km by 14 km of which over two-thirds are located in a narrow 5 km by 6-km zone. The hypocentral depths range from 2 to 11 km with over 90% deeper than 4 km. Single fault plane solutions were obtained for 35 events. Based on the focal mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Hypocentral depths of microearthquakes in the MPPSZ (Fig. 2) range from 1 to 12 km (Madabhushi and Talwani 1993;Chapman et al 2016). Studies of focal mechanisms from the MPSSZ show a wide variety of fault types and orientations (Madabhushi and Talwani 1993;Chapman et al 2016) that Marple and Hurd (2020, fig.…”
Section: Modern Seismicity In the Charleston Regionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hypocentral depths of microearthquakes in the MPPSZ (Fig. 2) range from 1 to 12 km (Madabhushi and Talwani 1993;Chapman et al 2016). Studies of focal mechanisms from the MPSSZ show a wide variety of fault types and orientations (Madabhushi and Talwani 1993;Chapman et al 2016) that Marple and Hurd (2020, fig.…”
Section: Modern Seismicity In the Charleston Regionmentioning
confidence: 99%
“…2) range from 1 to 12 km (Madabhushi and Talwani 1993;Chapman et al 2016). Studies of focal mechanisms from the MPSSZ show a wide variety of fault types and orientations (Madabhushi and Talwani 1993;Chapman et al 2016) that Marple and Hurd (2020, fig. 14) postulated is from small displacements along several faults east of the Summerville restraining bend.…”
Section: Modern Seismicity In the Charleston Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by Madabhushi and Talwani (1993) refined the earlier model by utilizing 58 additional well-recorded events in the Middleton Place-Summerville Seismic Zone from 1980 to 1991.…”
Section: Lower Coastal Plain -Middleton Place-summerville Seismic Zonementioning
confidence: 99%
“…Results of this effort demonstrated that the Ashley River and the Woodstock faults are not simple planar features, but resemble zones composed of short segments of varying strike and dip. Madabhushi and Talwani (1993) concluded that the seismicity in the Middleton Place-Summerville Seismic Zone defines the intersection of two fault zones, which they inferred to be the Ashley River fault zone and the Woodstock fault zone. Not felt except by a very few under especially favorable circumstances (I Rossi-Forel Scale).…”
Section: Lower Coastal Plain -Middleton Place-summerville Seismic Zonementioning
confidence: 99%